KETERAMPILAN MENULIS PARAGRAF INDUKTIF BAHASA INDONESIA SISWA KELAS XI SMA NEGERI 2 SOPPENG - Nur Sulis Ramadani; Dinaramdani; Nurcaya (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2022)
This study aims to obtain an objective picture of the ability of XI students of SMA Negeri 2 Soppeng in writing inductive paragraphs in Indonesian. The research method used is descriptive quantitative method. The sample in this study was taken only 50% or 82 students from a population of 164 people. The data analysis technique used is quantitative analysis technique, namely analyzing data in the form of a frequency distributive table. The results showed that, based on a predetermined percentage standard of 85%, after processing the data obtained, it turned out that the ability of class XI students of SMA Negeri 2 Soppeng to write Indonesian inductive paragraphs was not sufficient, because the results achieved by students were 73.41 %. It is hoped that the teacher can provide motivation and a deeper understanding for students in developing writing skills, especially writing paragraphs